Posture and movement characteristics of forward and backward walking in horses with shivering and acquired bilateral stringhalt. (20th April 2014) - Draper, A. C. E.; Trumble, T. N.; Firshman, A. M.; Baird, J. D.; Reed, S.; Mayhew, I. G.; MacKay, R.; Valberg, S. J.
Summary Reasons for performing study To investigate and further characterise posture and movement characteristics during forward and backward walking in horses with shivering and acquired, bilateral stringhalt. Objectives To characterise the movement of horses with shivering (also known as shivers) in comparison with control horses and horses with acquired bilateral stringhalt. Study design Qualitative video analysis of gait in horses. Methods Owners' and authors' videos of horses with shivering or stringhalt and control horses walking forwards and backwards and manually lifting their limbs were examined subjectively to characterise hyperflexion, hyperextension and postural abnormalities of the hindlimbs. The pattern and timing of vertical displacement of a hindlimb over one stride unit was evaluated among control, shivering and stringhalt cases. Results Gait patterns of shivering cases were characterised as follows: shivering‐hyperextension (‐HE, n = 13), in which horses subjectively showed hyperextension when backing and lifting the limb; shivering‐hyperflexion (‐HF, n = 27), in which horses showed hindlimb hyperflexion and abduction during backward walking; and shivering‐forward hyperflexion (‐FHF, n = 4), which resembled shivering‐HF but included intermittent hyperflexion and abduction with forward walking. Horses with shivering‐HF, shivering‐FHF and stringhalt (n = 7) had a prolonged swing phase duration compared with control horses and horses with shivering‐HE during backward walking. With the swing phase of forward walking, horses with stringhalt had a rapid ascent to adducted hyperflexion of the hindlimb, compared with a rapid descent of the hindlimb after abducted hyperflexion in horses with shivering‐FHF. Conclusions Shivering affects backward walking, with either HE or HF of hindlimbs, and can gradually progress to involve intermittent abducted hyperflexion during forward walking. Shivering‐HF and shivering‐FHF can look remarkably similar to acquired bilateral stringhalt during backward walking; however, stringhalt can be distinguished from shivering‐HF by hyperflexion during forward walking and from shivering‐FHF by an acute onset of a more consistent, rapidly ascending, hyperflexed, adducted hindlimb gait at a walk.